Kepemimpinan Intrapersonal Dan Implikasi Organisasional - Heru Kurnianto Tjahjono; Majang Palupi (Universitas Muhammadiyah Yogyakarta, 2015)
The study describes the intrapersonal leadership in a variety of organizational metaphors. The purpose of this study provides a conceptual constructs about intrapersonal leadership and the importance of intrapersonal leadership within the organization in a variety of perspectives. There are five metaphors, those are organisms, population ecology, transactional and power, the engine and psychological shackles. Recently studies have highlighted the importance of intrapersonal leadership in integrative view of the above five metaphors. This study provides the conceptual basis intrapersonal leadership and organizational implications of the hypothetical.